Water Diplomacy Frameworks in the Euphrates–tigris River Basin: a Theoretical Analysis - Kibaroğlu, Ayşegül (Institute of Political and International Studies, ELTE Faculty of Social Sciences, 2021)
Transboundary water politics in the Euphrates-Tigris (ET) basin is often marked with political confrontations and power asymmetries among its major riparians, namely Turkey, Syria and Iraq. However, a closer look into the case, by utilizing primary resources, demonstrates that the region also hosts water diplomacy governance mechanisms. Thus, the paper will analyze actors and processes in complex water diplomacy frameworks in the ET basin. Huntjens et al.’s1 Multi-track Water Diplomacy Framework (MWDF) intends to identify the key determinants for shifting water conflict into cooperation in transboundary rivers. It aims at delineating the key factors affecting current efforts by state and non-state actors to cooperate on transboundary water issues. The MWFD facilitates identification of political actors, institutions and processes that influence, and more often than not constrain, the effectiveness of transboundary cooperation. It also helps to diagnose water problems across sectors and administrative boundaries, and at different levels of governance. Thus, in this paper, the evaluation of water diplomacy frameworks in the ET basin is inspired by the MWDF’s conceptual framework, which analyses the interaction between the agent (state and non-state actors) and the structure (institutions) as well as the different outputs, outcomes and impacts as a result of that interaction. On the other hand, Klimes et al.2 defines “water diplomacy as a multi-disciplinary concept that draws on technical, political, and socio-economic knowledge; located at the intersect of science, policyand practice, and including both state and non-state actors.” In line with this broader definition, this paper provides an extensive analysis on water diplomacy actors, which comprises formal actors, such as States i.e. diplomats and technocrats as well as informal or non-state actors, which have an important role in water diplomacy dialogues as representatives of Track II initiatives, such as the NGOs, academia and think tanks.
Keywords: Water diplomacy frameworks; Euphrates–Tigris basin; Actors; Processes